HUBUNGAN TINGKAT PENGETAHUAN TENTANG TUBERKULOSIS PARU DENGAN MOTIVASI PASIEN DALAM MENJALANKAN PENGOBATAN DI PUSKESMAS UMBULHARJO 1 YOGYAKARTA - Merani, Alima Frida; Iskamto, Bambang; Rosyad, Yafi Sabila (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2021)
Background: Motivation is a strength, drive, need, pressure and a psychological mechanism that is forced to be an accumulation of internal and external factors. Knowledge also has an important role in pulmonary TB patients while undergoing pulmonary TB treatment. The Objective: To examine the relationship between the level of knowledge about pulmonary tuberculosis and the motivation of patients to carry out treatment at the Umbulharjo 1 health center in Yogyakarta. The Research Methods: This type of research is quantitative, the method used is correlation with cross sectional design approach. The population in this study were 46 people with up to 30 respondents taken using purposive sampling technique. The Results: Somer’s D correlation test results of .346 are smaller than 0.005, meaning that there is a significant relationship between the level of knowledge and patient motivation in undergoing treatment at the Umbulharjo 1 Health Center in Yogyakarta. The Conclusion: There is a relationship between the level of knowledge and patient motivation in undergoing treatment at the Umbulharjo 1 Health Center in Yogyakarta.